2012
DOI: 10.1021/jp2124108
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Effects of Na+ and K+ on the Thermal Stability of Na+,K+-ATPase

Abstract: Folding and structural stability are key factors for the proper biological function of proteins. Na(+),K(+)-ATPase is an integral membrane protein involved in the active transport of Na(+) and K(+) across the plasma membrane. In this work we characterized the effects of K(+) and Na(+) on the thermal inactivation of Na(+),K(+)-ATPase, evaluating both catalytic and transport capacities of the pump. Both activities of the enzyme decrease with the preincubation time as first-order kinetics. The thermal inactivatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 54 publications
0
27
0
Order By: Relevance
“…This was the case of several P-ATPases for which the kinetic coefficients describing the time course of the structural changes detected by Trp, ANS and eosin fluorescence, circular dichroism, and ion occlusion capacity are not statistically different from that corresponding to the inactivation process (Cattoni et al 2008;Kaufman et al 2012;Levi et al 2000;Placenti et al 2017), indicating that changes in the enzyme activity and secondary and tertiary structure are all part of the same global change produced by incubation at high temperatures.…”
Section: Kinetic Stability: the Two-state Irreversible Modelmentioning
confidence: 95%
See 4 more Smart Citations
“…This was the case of several P-ATPases for which the kinetic coefficients describing the time course of the structural changes detected by Trp, ANS and eosin fluorescence, circular dichroism, and ion occlusion capacity are not statistically different from that corresponding to the inactivation process (Cattoni et al 2008;Kaufman et al 2012;Levi et al 2000;Placenti et al 2017), indicating that changes in the enzyme activity and secondary and tertiary structure are all part of the same global change produced by incubation at high temperatures.…”
Section: Kinetic Stability: the Two-state Irreversible Modelmentioning
confidence: 95%
“…In P-type ATPases, it was found that the decrease in enzyme activity is paralleled by large changes in secondary and tertiary structure (Cattoni et al 2008;Kaufman et al 2012;Levi et al 2000;Placenti et al 2017). The irreversible loss of ATPase activity was not due to either degradation or formation of SDS-stable aggregates of the protein.…”
Section: The Thermally Induced Membrane Protein Denatured Statementioning
confidence: 99%
See 3 more Smart Citations